(untitled) (American Journal of Pedagogical and Educational Research, 2024)
Football is always a mystery, always a mystery. You can never predict how the match will turn out, who will be the winner. Along with this, football has another valuable quality — it is universal. Thus, systematic classes of schoolchildren in football provide comprehensive attention to the body, the functional activity of the body is improved, proper physical development takes place, and positive skills and character traits are formed.